An ultrastructural analysis of the effects of ethanol self-administration on the hypothalamic paraventricular nucleus in rhesus macaques - Jimenez, Vanessa A.; Helms, Christa M.; Cornea, Anda; Meshul, Charles K.; Grant, Kathleen A. (Frontiers in Cellular Neuroscience, 2015)
A bidirectional relationship between stress and alcohol exists whereby stressful events are comorbid with problematic alcohol use and prolonged alcohol exposure results in adaptations of the physiological stress response. Endocrine response to stress is initiated in the hypothalamic paraventricular nucleus (PVN) with the synthesis and release of corticotropin-releasing hormone (CRH) and arginine-vasopressin (AVP). Alterations in CRH and AVP following long-term alcohol exposure in rodents is well demonstrated, however little is known about the response to alcohol in primates or the mechanisms of adaptation. We hypothesized that long-term alcohol self-administration in nonhuman primates would lead to ultrastructural changes in the PVN underlying adaptation to chronic alcohol. Double-label immunogold electron microscopy was used to measure presynaptic GABA and glutamate density within synaptic terminals contacting CRH- and AVP-immunoreactive dendrites. Additionally, pituitary-adrenal hormones (ACTH, cortisol, DHEA-s and aldosterone) under two conditions (low and mild stress) were compared before and after self-administration. All hormones were elevated in response to the mild stressor independent of alcohol consumption. The presynaptic glutamate density in recurrent (i.e., intra-hypothalamic) CRH terminals was highly related to alcohol intake, and may be a permissive factor in increased drinking due to stress. Conversely, glutamate density within recurrent AVP terminals showed a trend-level increase following alcohol, but was not related to average daily consumption. Glutamate density in non-recurrent AVP terminals was related to aldosterone under the low stress condition while GABAergic density in this terminal population was related to water consumption. The results reveal distinct populations of presynaptic terminals whose glutamatergic or GABAergic density were uniquely related to water and alcohol consumption and circulating hormones.